Effect of Antenatal Anaemia of the Mother on the Volume of the Placenta (Anwer Khan Modern Medical College Journal, 2011)
In pregnancy, anaemia has a tremendous effect on the placenta. Maternal anaemia increases the volume of the placenta. Foetal hypoxaemia usually develops as a consequence of maternal anaemia, due to lower haemoglobin concentration, and stimulates placental growth. A prospective study was carried out in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital and Maternal and Child Health Training Institute (widely known as Azimpur Maternity), Dhaka, Bangladesh, from August 2005 to June 2006 on 60 Bangladeshi women who were within 35-40 weeks of gestation. Among them, 20 had normal uncomplicated pregnancies (considered as control group or group A) and another 27 had pregnancies with mild anaemia (considered as group B1) and 13 had pregnancies with moderate anaemia (considered as group B2). Severe anaemic (considered as group B3) mother was not found during the period of collection of data for this study. The mothers were selected as who were suffering from antenatal anaemia i.e. having heamoglobin level